What is Capnia umpqua Frison? (Plecoptera: Capniidae), distribution and variation of terminalia - Baumann, Richard W. (Illiesia, 2009)
Isoperla laucki sp. n. and I. karuk sp. n. are described from the Coast Range in northwestern California. Isoperla laucki is shown to be a peculiar member of the genus in western North America based on the male aedeagus, female egg and color pattern of the nymph. Isoperla karuk is included in the Isoperla marmorata complex, where it shares a sclerotized club-shaped process on the male aedeagus. Images of the male and eggs of both species and the female subgenital plate and nymphal mouth parts of I. laucki are provided as scanningelectron micrographs. A color photograph of the nymphal habitus of I. laucki is included. Distribution data are given for the confirmed specimens available of both species.
Keywords: Capniidae; entomology; new species; Capnia umpqua; California; Plecoptera; taxonomy; Oregon; distribution